Balancing climate goals and biodiversity protection: legal implications of the 30x30 target for land-based carbon removal - Philipp Günther; Philipp Günther; Philipp Günther; Felix Ekardt; Felix Ekardt (Frontiers in Climate, 2023)
This article examines the legal conflicts between land-based carbon dioxide removal (CDR) strategies and the establishment of protected areas through the lens of international environmental law. We argue that the 2022 Global Biodiversity Framework's “30x30” target—which aims to protect 30% of global terrestrial and marine areas by 2030—constitutes a “subsequent agreement” under international law and thus clarifies the legal scope and content of the obligation to establish protected areas under Article 8 of the Convention on Biological Diversity (CBD). Since states have pledged 120 million square kilometers for land-based CDR, these commitments potentially conflict with the “30x30” target, especially if global cropland for food production is to be maintained. Consequently, some land-based CDR strategies may directly or indirectly impede the achievement of the “30x30” target, which could be deemed inconsistent with international law. However, as all international environmental law operates in a continuum, this does not imply that land-based CDR should be categorically ruled out. Rather, states should focus on emission reductions and implementing CDR options that provide the most co-benefits to climate mitigation and biodiversity protection efforts.